Respuesta :

Answer:

-96 + 672\,i

Step-by-step explanation:

This is a product of complex numbers, so we have in mind not only the general rules for multiplying binomials, but also the properties associated with the powers of the imaginary unit "i", in particular [tex]i^2=-1[/tex]

We start by making the first product indicated which is that of a pure imaginary number (-6i) times the complex number (8-6i). We use distributive property and obtain the new complex number that results from this product:

[tex]-6\,i\,(8-6\,i)= (-6\,i)\,* 8 \, -\,6\,i\,(-6\,i)=-48\,i+36\,i^2=-48\,i+36\,(-1)=-36-48\,i[/tex]

Now we make the second multiplication indicated (using distributive property as one does with the product of binomials), and combine like terms at the end:

[tex](-36-48\,i)\,(-8-8\.i)=(-36)\.(-8)+(-36)(-8\,i)+(-48\,i)\,(-8)+(-48\,i)(-8\,i)=\\=288+288\,i+384\,i+384\,i^2=288+288\,i+384\,i+384\,(-1)=\\=288-384+288\,i+384\,i=-96+672\,i[/tex]

ACCESS MORE